Developing Narrative Text-Based Module for Teaching Reading Comprehension: Focus on Practicality : Developing Narrative Text-based Modul for Teaching Reading Comprehension - Safriyani Novitri (UIR Press, 2021)
This paper shows the function of a narrative text-based module to develop students reading skills. The research design is R & D (Research and Development), focusing on students' practicality. The researcher tried to find out the analysis and the practicality of the module in designing and implementing reading in a narrative text based-module. The sample was selected from second-semester students at the English Department of FKIP UIR. The students were given a test to be answered to find out the practicality, which consisted of pre-test and post-test. The module provides exercises that encourage the students to develop their reading comprehension. This module combines summary and references in every unit of the module. This module provides a formative test with an answer key at the end of each chapter.